2009
DOI: 10.1249/mss.0b013e31819ca07b
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue-Induced ACL Injury Risk Stems from a Degradation in Central Control

Abstract: Unilateral fatigue induces a fatigue crossover to the contralateral limb during single-leg landings. Central fatigue thus seems to be a critical component of fatigue-induced sports landing strategies. Hence, targeted training of central control processes may be necessary to counter successfully the debilitative impact of fatigue on ACL injury risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
182
3
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 150 publications
(201 citation statements)
references
References 41 publications
9
182
3
1
Order By: Relevance
“…Specifically, trunk movement patterns were altered, as evidenced as a result of fatigue, during a repetitive lifting task (Sparto et al, 1997). McLean & Samorezov (2009) also demonstrated that central fatigue is a key player in ACL injury risk upon fatigue-induced landing. Unilateral fatigue led to a fatigue crossover to the contralateral limb when performing single-leg landings, which altered landing strategies (McLean & Samorezov, 2009).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Specifically, trunk movement patterns were altered, as evidenced as a result of fatigue, during a repetitive lifting task (Sparto et al, 1997). McLean & Samorezov (2009) also demonstrated that central fatigue is a key player in ACL injury risk upon fatigue-induced landing. Unilateral fatigue led to a fatigue crossover to the contralateral limb when performing single-leg landings, which altered landing strategies (McLean & Samorezov, 2009).…”
Section: Introductionmentioning
confidence: 90%
“…McLean & Samorezov (2009) also demonstrated that central fatigue is a key player in ACL injury risk upon fatigue-induced landing. Unilateral fatigue led to a fatigue crossover to the contralateral limb when performing single-leg landings, which altered landing strategies (McLean & Samorezov, 2009). If asymmetries increase with fatigue, they may then partially explain this increase in injury risk.…”
Section: Introductionmentioning
confidence: 90%
“…Peripheral fatigue refers to a decrease in the ability of a muscle to produce force because of changes that occur at or distal to the neuromuscular junction, whereas central fatigue refers to an exercise-induced reduction in voluntary activation of a muscle because of changes that occur in a motor unit proximal to the neuromuscular junction. A recent study 54 provides evidence that central fatigue alone may be sufficient to produce measureable changes in lower extremity mechanics during single-leg landings. The reduction in gluteus medius activation latency we observed may also be the result of central fatigue effects, such as delayed anticipatory activation from the motor cortex or decreased a motor neuron conduction velocity from reduced excitability of the motor neuron membrane after repetitive activations.…”
Section: Electromyographymentioning
confidence: 99%
“…As noted earlier, decreased gluteus medius activation latency may be a consequence of some change in central control associated with participation in the isolated fatigue protocol. Some 54 have argued that targeted training of central control mechanisms may more effectively minimize the likelihood of altered lower extremity mechanics linked with ACL injury risk than interventions focused on strengthening alone. Indeed, adding visual feedback to a general lower extremity strengthening program has recently been found to elicit greater changes in frontal-plane hip kinematics during jumping than a strengthening program alone.…”
Section: Electromyographymentioning
confidence: 99%
“…Sagittal-plane knee mechanics were altered with fatigue; specifically, a decrease in knee flexion was seen at peak vertical ground reaction force, peak posterior ground reaction force, and peak knee flexion. Researchers who did not completely use a SLO-FP or FAST-FP but induced lower extremity fatigue found similar results for these kinematic variablesy, 12,20 An interesting result to note is the lack of difference between fatigue protocols (SLO-FP and FAST-FP). Most prefatigue to postfatigue changes were observed regardless of the fatigue protocol used, with minimal differences noted between the 2 protocols.…”
mentioning
confidence: 92%